Early Word Recognition in Sentence Context: French and English 24‐Month‐Olds' Sensitivity to Sentence‐Medial Mispronunciations and Assimilations. (26th April 2013) - Skoruppa, Katrin; Mani, Nivedita; Plunkett, Kim; Cabrol, Dominique; Peperkamp, Sharon
Abstract : Recent work has shown that young children can use fine phonetic detail during the recognition of isolated and sentence‐final words from early in lexical development. The present study investigates 24‐month‐olds' word recognition in sentence‐medial position in two experiments using an Intermodal Preferential Looking paradigm. In Experiment 1, French toddlers detect word‐final voicing mispronunciations (e.g., buz [byz ] for bus [bys ] "bus"), and they compensate for native voicing assimilations (e.g., buz d evant toi [buzd əvɑ̃twa] "bus in front of you") in the middle of sentences. Similarly, English toddlers detect word‐final voicing mispronunciations (e.g., sheeb for sheep ) in Experiment 2, but they do not compensate for illicit voicing assimilations (e.g., sheeb th ere ). Thus, French and English 24‐month‐olds can take into account fine phonetic detail even if words are presented in the middle of sentences, and French toddlers show language‐specific compensation abilities for pronunciation variation caused by native voicing assimilation.